Schematic Illustrations of Evolving Tholeiitic and Calc-Alkaline Magmatic Systems: New Models - Ihinger, Phillip D.; Brinza, Eric M. (My University, 2016)
The dramatic contrast in the geochemical evolution of tholeiitic and calc-alkaline magmatic systems has remained an enigma since their original characterization nearly a century ago. Recently, two new models that describe the evolution of each magma type have been developed that explain the enigmatic features observed in the classic intrusions of each magma type (Ihinger, 2015). The long-standing paradoxical observations within the tholeiitic Skaergaard (Greenland) and the calc-alkaline Shonkin Sag (Montana) intrusions are now understood to represent magma chambers wherein evolved felsic liquids have buoyantly segregated from a host residual crystal mush. Here, we present our efforts using Adobe Illustrator to schematically illustrate the processes that lead to the geochemical and textural variations observed in the crystallized intrusions. We support these illustrations with actual thin-section photomicrographs taken from the intrusions. Our images document the evolving geochemistry of both residual liquid and complementary crystal phases throughout the duration of crystallization. Our representations capture the details of the chemical evolution and show the roles that the processes of crystallization, liquid immiscibility, and compaction play in the development of each magma intrusion.
Color poster with text, images, and graphs.
Keywords: Posters; Calc-alkaline; Magma; Tholeiitic